2018
DOI: 10.31235/osf.io/xzqbe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patrilocal, Matrilocal or Neolocal? Intergenerational Proximity of Married Couples in China

Abstract: Objective: The study describes current patterns of intergenerational proximity in China, and analyzes the structural conditions that are associated with couples' proximity to the husband's and the wife's parents.Background: Patrilocality is a core aspect of the traditional Chinese kinship system,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Nearly half of older parents have adult children living nearby in the same neighborhood or the same county (Lei et al, 2015). Among non-coresident married couples, most of them live close to husbands’ or wives’ parents in the same community or district (Gruijters & Ermisch, 2019). The cultural value of familism continues to hold family members together and live their lives interdependently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nearly half of older parents have adult children living nearby in the same neighborhood or the same county (Lei et al, 2015). Among non-coresident married couples, most of them live close to husbands’ or wives’ parents in the same community or district (Gruijters & Ermisch, 2019). The cultural value of familism continues to hold family members together and live their lives interdependently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Daughters are now as likely as sons to provide financial support to parents in China, at least in urban areas (Hu 2017; Lei 2013; Xie and Zhu 2009). Parents living with sons is still dominant, but there are signs that norms of patrilocal residence are eroding (Gruijters and Ermisch 2019; Chen 2005; Chen and Short 2008; Xie and Zhu 2009). To my knowledge though, no studies have assessed if the growth of sonless families contributed to such broader changes.…”
Section: Background and Conceptualizationmentioning
confidence: 99%
“…Instead, it is argued that economic development and social change shift the needs and capacities of both parent and child and, subsequently, the co-residence patterns we observe (Xu et al, 2014). For example, it has been shown that the child's needs tend to override parental needs in determining whether a child co-resides with his or her parent in urban China (Gruijters and Ermisch, 2018;Zhu and Xie, 2017). This appears to contradict studies conducted in more rural, traditional parts of China (Gruijters and Ermisch, 2018;Logan and Bian, 1999;Zhang, 2004).…”
Section: Existing Researchmentioning
confidence: 99%
“…For example, it has been shown that the child's needs tend to override parental needs in determining whether a child co-resides with his or her parent in urban China (Gruijters and Ermisch, 2018;Zhu and Xie, 2017). This appears to contradict studies conducted in more rural, traditional parts of China (Gruijters and Ermisch, 2018;Logan and Bian, 1999;Zhang, 2004). Following this line of argument suggests that explaining differences between European and Chinese intergenerational co-residence requires an understanding of how needs and capacities are shaped by structural, macro-level context.…”
Section: Existing Researchmentioning
confidence: 99%